Pergeseran Nilai-Nilai Islam & Budaya Dalam Tradisi Nyongkolan Adat Sasak (Studi Pada Kegiatan Nyongkolan Menggunakan Kesenian Kecimol) - Burhanudin; Heriyadi (Ulul Albab: Journal Da`wah and Social Religiosity, 2024)
Kecimol is contemporary art which is a product of today as part of cultural acculturation due to interactions with other cultures. The cultural acculturation referred to is European culture which started from drum bands and then the idea emerged to form a new art known as Kecimol. This research aims to find out how Islamic and cultural values have shifted in the nyongkolan tradition using kecimol. The research method used is a qualitative approach which produces a clear description and the data obtained is in accordance with the desired data so that it can be analyzed well. This research found that the shift in Islamic values is 1) the presence of dancers, 2) the presence of alcohol which causes commotion, 3) dirty words, 4) loss of mutual respect with road users. Apart from that, the cultural shift that occurred was 1) how to dress, 2) how to line up, 3) when to finish hanging out.